2020
DOI: 10.3389/fsens.2020.583822
|View full text |Cite
|
Sign up to set email alerts
|

Grand Challenges in Nanomaterial-Based Electrochemical Sensors

Abstract: Electrochemical sensors have an enormous potential in a wide variety of environmental, industrial, and medicinal applications. Apart from the immense success of glucose sensors, much more work is still needed in order to make electrochemical sensors have a widespread impact and application. For example, the current circumstances of the COVID-19 pandemic demonstrated the importance and urgency of having accurate and rapid diagnostic devices (Jiang et al., 2020). The advancement of sensors could truly help stop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 30 publications
(35 reference statements)
0
28
0
Order By: Relevance
“…There are mainly three major hurdles encountered in the development of electrochemical sensors: the attainment of a low limit of detection (LOD); limiting the interaction of unwanted interfering species; maintaining sensor stability and achieving reproducibility in complex real matrices [27]. The LOD indicates the lowest concentration/quantity that could be detected for an analyte and is a major criterion for a sensor performance as many times we are dealing with analytes that are present at trace levels in real samples.…”
Section: Voltammetric Sensorsmentioning
confidence: 99%
“…There are mainly three major hurdles encountered in the development of electrochemical sensors: the attainment of a low limit of detection (LOD); limiting the interaction of unwanted interfering species; maintaining sensor stability and achieving reproducibility in complex real matrices [27]. The LOD indicates the lowest concentration/quantity that could be detected for an analyte and is a major criterion for a sensor performance as many times we are dealing with analytes that are present at trace levels in real samples.…”
Section: Voltammetric Sensorsmentioning
confidence: 99%
“…However, they are not yet ready to be utilized as a regular analytical tool in food corporations because the technology is in its infancy. The major obstacles faced in the development of electrochemical sensors are as follows: (1) achieving a low limit of detection (LOD); (2) nullifying non-specific adsorption of interfering species; (3) on-site detection of samples, or conversion of a sensor into a point-of-care device; (4) preserving the sensor’s stability and repeatability in complicated actual matrices [ 114 ]. Furthermore, when the analyte is a biological sample, i.e., bacteria, differentiation between living and dead cells is a major challenge.…”
Section: Challenges In Development Of Electrochemical Sensors Against...mentioning
confidence: 99%
“…Because it is impossible to evaluate every sensor generated in mass-production facilities, sensor-to-sensor repeatability is critical during the manufacturing process. Instead, when the sensors are manufactured, statistical sampling of a portion of the sensors is carried out, and the testing and calibration findings should be relevant to the entire batch [ 114 ]. Hydrogels, rubber-like composites, new polymers and organo-gels are often used to create tiny sensors with high stability.…”
Section: Challenges In Development Of Electrochemical Sensors Against...mentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the efficiency of electrochemical devices, the ionic conductivity of the materials and solvent media play an important role in enhancing the performance of these devices [ 52 ]. It can be observed that the electrolyte possesses high electron mobility and low viscosity, which could result in a high electrochemical stability frame.…”
Section: Introductionmentioning
confidence: 99%